CXCR4 antagonist inhibits perineural invasion of adenoid cystic carcinoma. Issue 11 (12th August 2014) - Jeong, Woo-Jin; Choi, Ik Joon; Park, Min-Woo; An, Soo-Youn; Jeon, Eun-Hui; Paik, Jin Ho; Sung, Myung-Whun; Ahn, Soon-Hyun
Abstract : Aim: Perineural invasion and expression of CXCR4 is characteristic of adenoid cystic carcinoma (ACC). Herein, we aimed to demonstrate CXCR4 expression in ACC, identify its association with perineural invasion and investigate the impact of CXCR4 inhibitor in vitro and in a murine perineural invasion model. Methods: Expression of CXCR4 was assessed in ACC cell lines and in human tissue. The effects of gene knockdown using siRNA and specific blocker of CXCR4 (AMD3100) were evaluated in vitro. A preclinical perineural invasion model was developed using BALB/c nude mouse. The effect of AMD3100 was evaluated in vivo. Results: CXCR4 was highly expressed in aggressive strains of ACC in vitro, in the tumour in the animal model and in the tumour of human tissue. SDF-1 expression was also demonstrated in the nerve of murine and human tissue. Gene knockdown by siRNA and inhibition by a CXCR4-specific inhibitor AMD3100 effectively abrogated invasion but not proliferation of ACC in vitro. The rate of perineural invasion was significantly decreased with AMD3100 treatment in the animal model. Conclusions: CXCR4 is associated with perineural invasion in ACC. AMD3100, which can effectively diminish perineural invasion of ACC, may have an adjuvant role in the management of ACC.